The effect of concentrated loads on open-well masonry spiral stairs. (1st December 2022) - Olivieri, Carlo; Iannuzzo, Antonino; Fortunato, Antonio; DeJong, Matthew J.
Abstract: Concentrated loads applied on masonry open-well spiral stairs affect the compressive stress regime and, more importantly, may change the stress distribution drastically, producing undesirable torsional effects on the steps. Depending on geometry, materials, and construction technology, their application may compromise the stair stability. The current literature on the argument usually considers only uniformly load distribution, while the case of localised loads has not received any attention. The present paper aims to fill this gap by adopting a simplified method as an analytical tool, namely the Linear Arch Static Analysis (LASA), recently introduced and applied to analyse the structural behaviour of open-well spiral stairs under constant loads. An extensive parametric analysis of stairs with circular and elliptical planforms is carried out to define meaningful ranges of geometric stair parameters and concentrated load positions, ensuring safety against collapse. Lastly, to demonstrate the efficiency of the proposed approach to concentrated loads, the LASA method is applied and compared with a rigid block model on a real case study, represented by the stair in the Convent of San Domingo de Bonaval. Here the steps touch each other at their inner end, forming a virtual rib that transmits the external loads to the ground. Pros and cons of adopting the proposed procedures are highlighted, showing how LASA represents a simple but effective method to evaluate compressive equilibrium solutions for any stair geometry and vertical load distributions.